Formulation and Evaluation of Clove Flower Extract (Syzygium aromaticum L.) Toothpaste Aidie With Variations of NA CMC Concentration as a Binder - Herawayanti, Sinta; Indriastuti, Marlina (Mukhtabar Journal of Medical Laboratory Technology, 2025)
Background & Objective: Toothpaste is a semi-solid preparation that contains abrasives, cleansers, and additives to clean teeth without damaging oral tissues. Clove flower (Syzygium aromaticum L.) is known to contain eugenol, saponins, and flavonoids, which are analgesic. The purpose of this study was to make and evaluate toothpaste preparations from clove flower extract. Method: The research was conducted experimentally with toothpaste formulation using variations in Na CMC concentration as a binder: 2%, 1%, and 0.5%. Evaluation included organoleptic test, homogeneity, pH, viscosity, spreadability, foam formation, and physical stability. Data were analyzed using SPSS. Result: All formulas met the evaluation standards. Formula I was closest to the positive control in organoleptic, having an average viscosity of 9600 mPa.s and spreadability of 5.2 cm. Formula II showed the best pH with an average of 8.74. All three formulas produced foam well. Physical stability for 4 weeks showed that the texture and pH remained stable. Conclusion: Na CMC affects the viscosity and spreadability of toothpaste preparations. Formulas with the right concentration of Na CMC can produce herbal toothpaste that is stable and meets quality requirements.